Performance analysis of IoT protocol under different mobility models. (November 2018) - Kabilan, K.; Bhalaji, N.; Selvaraj, Chithra; Kumaar B, Mahesh; P T R, Karthikeyan
Abstract: Internet of Things [IoT] is a network that encompasses sensors, actuators and networking devices for the purpose of communication and control. The IoT devices are resource-constrained which require a specialized routing protocol in order to transmit the sensed data from source to destination efficiently. The IPv6 Routing Protocol for Low power and Lossy network (RPL) is one of the widely used routing protocols in IoT networks. The performance of RPL protocol is evaluated on the three different mobility models; Manhattan Grid (MG), Gaussian Markov (GM) and Random Waypoint (RW) at different scalability levels in Contiki based Cooja simulator. The standard Quality of Service (QoS) parameters; Packet Delivery Ration (PDR), Average Power (Pavg) and Hop Count (HC) are considered for analysis. The extensive experimental analysis of RPL when exposed to different mobility model and scalability reveals that, the Manhattan Grid model provides better QoS performance by preserving the working nature of RPL optimally.